Researcb on PCI Self-Configuration Tecbnology of LTE eNB System - Xiaoguang Zhu; Hua Jiang (Dianxin kexue)
PCI is an important LTE wireless parameter and impacts LTE network planning and network performance. The PCI self-configuration technology of LTE eNB system was mainly discussed, including the realization of SON architecture, self-configuration flow, the PCI resource planning and allocation strategies. The PCI self-configuration technology of LTE eNB system improves the LTE network deployment efficiency, enhances the performance of LTE network system, and reduces manual planning and operation.